EVOLUTION AND MAIN PRINCIPLES OF ISLAMIC FINANCE - Asror Komilov (Journal Park Publishing, 2022)
Nowadays one cannot imagine a country without its financial market. It plays a vital role for an economy to develop. Countries trying hard to expand their financial market. As it can be seen from the graph below, the global financial market is on the constant increase. Thus, it contributes to increase in GPD of the country, assisting to achieve a more sustainable economic growth.